2017
DOI: 10.1080/21693277.2017.1374894
|View full text |Cite
|
Sign up to set email alerts
|

An integrated tool to support sustainable toy design and manufacture

Abstract: Whilst the importance of considering the positive societal benefits of a product, in addition to other social, economic and environmental factors, has received wider recognition, its definition, concept, and integration into product design are not so well developed and studied. A literature review on sustainable design identified the potential of Social Life-Cycle Assessment as a tool to measure societal benefits of products; however further analysis of sustainable assessment methods highlighted the lack of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the case of PSIA, three case studies were identified even though some other cases using this approach were excluded since there were not scientific journal articles but corporate reports or conference proceedings. The other methodologies, i.e., FELICITA (Kouloumpis and Azapagic 2018), RESPONSA (Siebert et al 2018b), and SBA (Shin and Colwill 2017), correspond to very specific cases, just one of each one, and they were developed due to particular necessities of the industry and scope boundaries.…”
Section: Social Lca Methodologiesmentioning
confidence: 99%
“…In the case of PSIA, three case studies were identified even though some other cases using this approach were excluded since there were not scientific journal articles but corporate reports or conference proceedings. The other methodologies, i.e., FELICITA (Kouloumpis and Azapagic 2018), RESPONSA (Siebert et al 2018b), and SBA (Shin and Colwill 2017), correspond to very specific cases, just one of each one, and they were developed due to particular necessities of the industry and scope boundaries.…”
Section: Social Lca Methodologiesmentioning
confidence: 99%
“…A brief description of each category is brought in the following as well as the statistics of the papers covering the three category is shown in table 1 and figure 3. (Lillehagen & Petersen, 2015); (Caruso, Dumbacher, & Grieves, 2010); (Tagliaferri et al, 2016); (Atwater & Uzdzinski, 2014); (Garcia-Herrero et al, 2017); (Haanstra, Toxopeus, & van Gerrevink, 2017); (Jayal, Badurdeen, Dillon, & Jawahir, 2010); (Jawahir et al, 2006); (Gutowski et al, 2005); (Güçdemir & Selim, 2017); ; (Santucci & Esterman, 2015); (Rezvan, Azadnia, Noordin, & Seyedi, 2014); (Shin & Colwill, 2017); (Mani, Larborn, Johansson, Lyons, & Morris, 2016); (Haapala et al, 2013); (AlKhazraji, Saldana, Donghuan, & Kumara, 2013); (Hassan, Saman, Mahmood, Nor, & Rahman, 2016); (Huang & Badurdeen, 2017); (Lu et al, 2011); (Ranky, 2010); (Li, Mirlekar, Ruiz-Mercado, & Lima, 2016); (Bakshi, 2014); (Grünwaldt, Hofstetter, & Palm, 2011); (Shi & Yang, 2003); (Petnga & Austin, 2014); (Faezipour & Ferreira, 2011); (Salama, Galal, & Elsayed, 2015);…”
Section: Sustainable Manufacturing Grouping (Systems)mentioning
confidence: 99%